Emotional assessment in people exposed to violent situations: an exploratory analysis - Iván Ricardo Perdomo Vargas (Interacciones)
Introduction: Non-pathological effects on humans related to violence naturalization, bring forward a pronounced research interest related specifically to behavioral regulation mechanisms such as emotions. In this sense, the present work seeks to understand the extent of exposure to violent circumstances on the evaluation of emotional situations. Method: Eighty participants with ages between 18 and 30 years old resident in Villavicencio city (Colombia) participated. The sample was organized in two groups using My ETV (My Exposure to Violence) questionnaire: (1) those with greater exposure to violence and (2) those with less exposure. Later, participants evaluated the experienced level of emotion using the IAPS (International Affective Picture System) validated sets of images in Colombian population. Results: There are no significant differences in emotional assessment among groups. However, there are gender differences in terms of valence evaluation. Conclusions: It is necessary to join conceptual and methodological efforts to understand variations in the emotional response considering contexts peculiarities in which those responses emerge.